Tafsir Ayat Ayat Tentang Pendidikan Yang Dijadikan Landasan Dalam Membangun Jiwa Pendidik - Nur Hidayati, Desta Pratami; Khairi, Miftahul; Ummah, Khaira (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2025)
Educators in the understanding of Islamic teachings are people who have optimal responsibility for advancing, developing and guiding students' physical and mental potential to achieve their life goals and all the consequences based on Islamic values. Educators are also spiritual parents for their students, providing spiritual nourishment through knowledge and the development of noble morals. Educators have a higher dignity than prophets and apostles. The requirements to become an educator according to Islam are professional, mature, physically healthy, with an Islamic and spiritual personality, as well as an Islamic personality.